3-Deoxysappanchalcone attenuates LPS-induced neuroinflammation in microglia cell culture and ameliorates cognitive impairment in traumatic brain injury - Zemeng Li; Dangli Ren; Jingjing Wang; Yatao Wang; Yueyang Chen; Yunfeng Diao; Jianwei Li; Yang Qu; Maohua Zheng; Hongtao Sun (PLoS ONE, 2025)
Background As one of the major public health security problems, traumatic brain injury (TBI) is characterized by cerebral dysfunction. The following neuroinflammation is considered as the main secondary injury factor. Targeting the expression of inflammatory cytokines could be effective in alleviating TBI-induced neuroinflammation. The anti-inflammatory role of natural products is increasingly receiving attention. 3-Deoxysappanchalcone (3-DSC) is a bioactive compound from Caesalpinia sappan L. Methods The present study was designed to investigate the impact of 3-DSC on neuroinflammation in primary microglia and TBI models. To assess cytotoxicity, cell viability tests were conducted with varying concentrations of 3-DSC ranging from 5 to 20 μM. Quantitative PCR (qPCR) and Enzyme-Linked Immunosorbent Assay (ELISA) were utilized to measure the production of inflammatory cytokines in LPS-activated primary microglia treated with or without 3-DSC (at 10 μM). Immune blotting arrays were used to examine the activation of canonical inflammation signaling pathways. To further elucidate the anti-inflammation effect of 3-DSC, RNA-seq was carried out between LPS and LPS + 3-DSC group. In vitro co-culture experiments were carried out to evaluate the protective effect of 3-DSC on neurons against inflammation-mediated apoptosis. Additionally, in vivo experiments were performed to observe the impact of 3-DSC on TBI-induced microglia activation and spatial memory impairment. 3-DSC (160 μg/kg, 320 μg/kg) were administered via the tail vein at day 1 after TBI (n = 6). Behavioral tests were conducted 7 days after traumatic brain injury (TBI) to detect the spatial memory ability of rats. Results The cell viability results revealed that within the concentration range of 5–20 μM, 3-DSC did not cause significant cytotoxicity. In the qPCR and ELISA assays, it was found that 3-DSC at 10 μM led to a reduction in the production of inflammatory cytokines. The immune blotting arrays demonstrated that 3-DSC inhibited the activation of NF-kB and MAPK signaling pathways. The results of RNA sequencing revealed the altered signaling pathways and key hub genes. The in vitro co-culture outcomes indicated that 3-DSC could safeguard neurons from apoptosis caused by neuroinflammation. Finally, the in vivo experiments showed that 3-DSC was effective in alleviating TBI-induced microglia activation and spatial memory impairment. Discussion Collectively, these findings suggest that 3-DSC holds promise as a potential compound for the development of therapeutic and preventive agents aimed at treating neuroinflammation-related disorders. It offers a new avenue for further research and potential clinical applications in the context of TBI and neuroinflammation related disorders.